Väterliche Präsenz - ein Rahmenmodell mit vier Ebenen - Cierpka, Manfred; Eickhorst, Andreas; Benz, Marisa; Scholtes, Kerstin (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2010)
A framework model for paternal presence is introduced, which is meant to assist the integration of the often times confusing magnitude of theoretical findings of contemporary father research. The presented model includes a biological, an intrapersonal, an interpersonal as well as a family level. The levels are based on and contain one another. Each level discusses facets of how is fatherhood represented in fathers as well as actual quantitative and qualitative engagement.
Published online: 11 Feb 2014
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 06.03.2023